Pengaruh Model Think Pair and Share (TPS) Berbantuan LKPD dilengkapi Mind Map Terhadap Kompetensi Belajar Siswa - Imron, Muhamad; Yarmalinda, Dwi; Lirhan, Lirhan (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2023)
The purpose of this study is to determine the effect of cooperative learning model type of LKPD-assisted Think Pair and Share (TPS)equipped with Mind Map to learners' learning competencies. This research is a quasi experimental research. The population of this study were students of grade X SMAN 2 Siak upstream registered in the academic year 2023/2024. Sampling was done by using Simple Random Sampling technique and obtained class X2 as experiment class and class X1 as control class. instruments used in the form of objective tests and observation sheets. data analysis techniques to test the hypothesis are t-test, two-way anova test and Mann Whitney U test. Based on the results of data analysis and discussion, obtained some conclusions, namely: learning competencies cognitive, affective, and psychomotor learners who follow cooperative learning model type LKPD-assisted Think Pair and Share (TPS)equipped with Mind Map is better than learners who follow the learning conventional. The average value of initial ability of experimental class students 63,14 with high category while control class 60,23 with low category. The average value of Competence in the Cognitive Area of the experimental class was 82.54 with a total of 25 and 5 unfinished participants while the control class with an average score of 62.17 the number of students who completed 5 people and the unfinished 25 people. The average score of Competence The affective class of experimental class is 89.10 with good category while the control class with the average value is 63,80 with the less category. The average value of Competence in the Aspects of Psychomotor in experimental class is 89.50 with good category while control class is 64,81 with less category. There is an interaction between the learning model with the initial ability of learners in influencing the learning competence of the cognitive domain of the learners.